SG-CIM model application method in data middle platform - Qiming WAN; Sining WANG; Xin HE (Dianxin kexue)
The overall framework of State Grid ubiquitous power IoT and the layered architecture of data middle platform were analyzed.The positioning and application mode of SG-CIM in data middle platform,and the support of model for data analysis application were studied.The physical model design of data middle platform was put forward,on the premise of adopting the baseline version control,parallel expansion tables and joint views was created for personalized model expansion design.As to the integrated implementation of model data for data middle platform,combining database selection and adopt bulk data loading was proposed,so as to improve efficiency of data integration.As for the upgrading and updating of data middle platform model,creating a middle table to minimize the impact on the data analysis application was recommended,and a good support was achieved for the data analysis application based on data middle platform.